Serum miR-375 Levels Are Closely Related to Disease Progression from HBV Infection to HBV-Related Hepatocellular Carcinoma. (21st April 2020) - Zhang, Weilu; Fu, Ting; Guo, Zhenjun; Zhang, Ye; Zhang, Lei; Su, Haixia; Long, Yong; Ji, Zhaohua; Yan, Yongping; Shao, Zhongjun
Abstract : Background . There is an urgent need to identify ideal serological biomarkers that not only are closely related to disease progression from hepatitis B virus (HBV) infection to hepatocellular carcinoma (HCC) but also have high specificity and sensitivity. We conducted this study to analyze whether miR-375 has a potential value in the early prediction of the progression from HBV-related hepatitis or cirrhosis to HCC. Methods . A total of 177 participants were enrolled. Receiver operating characteristic (ROC) curve was used to evaluate the predictive capability of selected miR-375 for HBV-HCC. We upregulated the miR-375 expression in HepG2, HepG2.2.15, and HepAD38 cells to determine its effect on cellular proliferation and migration, in vitro using Cell Counting Kit-8 (CCK-8) assays. Results . Serum miR-375 levels decreased in order from healthy controls to chronic hepatitis B (CHB) without cirrhosis, followed by cirrhosis, and finally, HBV-HCC patients. miR-375 levels were significantly lower in HBeAg-positive and HBV DNA-positive patients than negative (P < 0.05 ) and significantly lower in patients with elevated alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA) than normal levels (P < 0.05 ). miR-375 might be a biomarker for HBV-HCC, with a high area under the curve (AUC) of 0.838 (95% confidence interval (CI) 0.780 to 0.897; sensitivity: 73.9%; specificity: 93.0%). The AUC (0.768 vs. 0.584) and sensitivity (93.8% vs. 75.0%) for miR-375 were higher than those for AFP. The overexpression of miR-375 noticeably inhibited proliferation and migration in HepG2, HepG2.2.15, and HepAD38, especially in HepG2.2.15 and HepAD38, which are stably infected with HBV. Conclusions . Serum miR-375 levels are closely related to disease progression from HBV-related hepatitis or cirrhosis to HCC.